The relationship between psych alienation and sport achievement motivation for students of sport talented school in Cairo, Egypt - "a comparative study" - Abd El Moneim, Z.; Al Sharkawy, M. A. (Science, Movement & Health, 2014)
The purpose of this study was to identify the level of psych alienation, sport achievement motivation and correlation between psych alienation and sport achievement motivation for students of sport talented school in Cairo, Egypt, Ages between 13-18 years, individual(n=42) and football (n=5) sports. Search tools were Sport achievement motivation inventory and Scale of Psych alienation. Methods. Subjects are between 13-18 years, individual(n=42) and football (n=5) sports groups. The results showed differences in favor of football talented on lack of meaning, motive of success achievement and sport achievement motivation, and inverse negative correlation between psych alienation and sport achievement motivation, the findings support need to conviction of utmost importance of psychological preparation for sport talented students from Officials of sport talented school, commitment to equality and justice in all the privileges offered to all sports alike according to the effort not to sport type, and provide study care for those talented because of its positive impact on the progress of their sport levels. Conclusion. There is a relationship between psych alienation and sport achievement motivation for students of sport talented school in Cairo.